Migration and Discrimination IMISCOE Short Reader - Fibbi, Rosita (IMISCOE Research Series, 2021)
This open access short reader provides a state of the art overview of the discrimination research field, with particular focus on discrimination against immigrants and their descendants. It covers the ways in which discrimination is defined and conceptualized, how it is measured, how it may be theorized and explained, and how it might be combated by legal and policy means. The book also presents empirical results from studies of discrimination across the world to show the magnitude of the problem and the difficulties of comparison across national borders. The concluding chapter engages in a critical discussion of the relationship between discrimination and integration as well as pointing out promising directions for future studies. As such this short reader is a valuable read to undergraduate students, as well as graduate students, scholars, policy makers and the general public.